If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = x + -14 Reorder the terms: 5 + 6x = x + -14 Reorder the terms: 5 + 6x = -14 + x Solving 5 + 6x = -14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 6x + -1x = -14 + x + -1x Combine like terms: 6x + -1x = 5x 5 + 5x = -14 + x + -1x Combine like terms: x + -1x = 0 5 + 5x = -14 + 0 5 + 5x = -14 Add '-5' to each side of the equation. 5 + -5 + 5x = -14 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = -14 + -5 5x = -14 + -5 Combine like terms: -14 + -5 = -19 5x = -19 Divide each side by '5'. x = -3.8 Simplifying x = -3.8
| (8+u)(4u+1)=0 | | x^2+12ax+35a^2=0 | | X^2+6x+43=0 | | 68=6x+6x+8 | | 9x-8=2x+34 | | -2z^2+5z+3=0 | | 3(y-5)+1=2y+34-2y | | -5x-3y-5x-8y= | | -43=-61+x | | 4ay/3d | | (x+y)=80 | | 2x^2-8x-100=20 | | X/27/2 | | x^3-8x^2-33x+26=0 | | 5z-6+6=-36+z | | 9a+2a-8a-3b= | | 29b-93=7 | | 5(2x-10)/2 | | 3x+7=9x+5 | | 4v^2+25v+21=0 | | 16a+8b+1=0 | | 12-b=0 | | (-7b-2c)+(6b-3c-1)= | | X+3x+(x+7)=32 | | 8a(-3a)= | | 50=1.75x | | -((-3)+3)= | | 5x+8=9x-8 | | 16a+8a+1=0 | | b(b-3)=28 | | 0=-16x^2+1400 | | 12=780x |